Vermittlungsgutscheine und Beauftragungen Dritter im Vergleich - Friedhelm Pfeiffer; Henrik Winterhager (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
– This paper makes a direct comparison of the relative effectiveness of job placement vouchers and the contracting out of placement services. The study is based on the process data of the Federal Employment Agency (Bundesagentur für Arbeit) and refers to the year 2004. The proportion of people who are in employment subject to social security contributions during the six months following the use of the instruments is regarded as the target variable. The results of the microeconometric comparison indicate that placement vouchers have put back into work more unemployed people who are legally entitled to use both instruments than the contracting out of placement services.
Keywords: 330; Arbeitsvermittlung - Erfolgskontrolle; Vermittlungsgutschein; private Arbeitsvermittlung; berufliche Reintegration; Beschäftigungseffekte